Three-dimensional correlation of speckles in deep Fresnel region: extracting the roughness exponent of random surface - Chunxiang Liu; Yu Zhang; Qingrui Dong; Li Ma; Yuqin Zhang; Zijun Zhan; Xing Li; Chuanfu Cheng (New Journal of Physics, 2019)
We provide a detailed analysis of the three-dimensional cross correlation properties of speckle patterns in the deep Fresnel region scattered by random surface. Basing on Kirchhoff approximation, we first derive the quantitative relationship between the longitudinal correlation function and the fractal characteristics of random surface. A novel measuring method is proposed for extracting the roughness exponent of random surface from the longitudinal correlation function of speckles. In experiment, the speckle patterns deviating different distance from the object plane are acquired by a microscopic imaging system. The longitudinal correlation function of the speckles descends with the increase of deviating distance in the form of negative power law. By calculating the Fourier transform of the longitudinal correlation function, we obtain the roughness exponent of random surface by making linear fitting in the large spectrum region. The extracted results are in good agreement with those measured by an atomic force microscopic, which indicate our method has a satisfying accuracy.